2008
DOI: 10.1016/j.jss.2007.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Is Hashimoto's Thyroiditis a Risk Factor for Papillary Thyroid Cancer?

Abstract: Background-Hashimoto's thyroiditis is the most common cause of hypothyroidism and is characterized by gradual autoimmune mediated thyroid failure with occasional goiter development. Hashimoto's (HT) is seven times more likely to occur in women than in men. Papillary thyroid cancer (PTC), the most prevalent form of cancer in the thyroid, is 2.5 times more likely to develop in women than men. Given the relatively high prevalence of these diseases and the increased occurrence in women, we analyzed data from our i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
166
1
16

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(195 citation statements)
references
References 13 publications
12
166
1
16
Order By: Relevance
“…A total of 38 articles satisfied the eligibility criteria (3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40). The eligible studies consisted of 37 case-control studies and one cohort study, all of which were hospital based.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 38 articles satisfied the eligibility criteria (3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40). The eligible studies consisted of 37 case-control studies and one cohort study, all of which were hospital based.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies investigated the frequencies of HT in PTCs and in other carcinomas such as follicular carcinoma and medullary carcinoma (3,5,8,10,11,13,14,15,16,17,18,19,20,21,22,23). HT was present in 797 (17.1%) of 4664 PTC patients and in 57 (7.9%) of 725 other carcinoma patients.…”
Section: Ptc Vs Other Carcinomasmentioning
confidence: 99%
See 1 more Smart Citation
“…A tireoidite de Hashimoto é a causa mais frequente de hipotireoidismo em áreas do mundo onde os níveis de iodo são adequados. Vários investigadores detectaram incidência aumentada de carcinoma papilífero da tireoide em pacientes com tireoidite de Hashimoto (5,8,10,16,22,25,28) . Os dados obtidos nesses estudos levantam a possibilidade de que a associação entre as duas doenças seja mais do que incidental, sugerindo a tireoidite como uma lesão precursora da neoplasia (18,25) .…”
Section: Introductionunclassified
“…On the other hand the data from male patients did not yield statistically significant results most probably due to the small sample size. The authors concluded that there was a trend in HT patients for the coexistence of PTC; a finding that becomes statistically significant in female HT patients that have 30% increased risk of having PTC compared to women without HT [11].…”
Section: Hashimoto's Thyroiditis and Papillary Thyroid Cancermentioning
confidence: 99%